Recent Advances in Direct Adhesive Restoration Resin-Based Dental Materials With Remineralizing Agents - Mai, Sui; Zhang, Qi; Liao, Muzi; Ma, Xinyue; Zhong, Yewen (Frontiers in Dental Medicine, 2022)
Resin-based dental materials are popular restorative materials especially in direct adhesive restoration because of the excellent mechanical and esthetic properties. Toward the realization of minimally invasive dental procedures, direct composite resin adhesive restoration has become the main treatment for dental defects. In addition, for caries-affected dentin close to the pulp, conservation remineralization has been advocated to save the living pulp. However, the resin–dentin interface can be destabilized by various factors, especially the enzymatic degradation of collagen fibrils within the hybrid layer and polymer hydrolysis. Furthermore, for resin-based restorative materials, the marginal gap remains a major problem that can lead to the occurrence of secondary caries. To address these issues, research efforts have focused on the remineralization of mineral-depleted dental hard tissues using remineralizing bioactive substances. In this review, we first described various bioactive agents with remineralizing properties. Furthermore, we discussed recent advances in resin-based dental materials for enamel or dentin remineralization. Finally, we examined the current challenges and prospects of these emerging materials. This work aims to provide a theoretical foundation for the future development of resin-based dental materials in direct adhesive restoration with remineralizing agents.